Predictive factors for biochemical relapse in non-metastatic prostate cancer following primary radiotherapy - Amila Kovčić; Šefika Umihanić; Hasan Osmić; Almedina Muhić; Enida Trumić; Eldar Hamzić; Emir Becirovic; Semir Hadžić; Amir Bećirović; Minela Becirovic; Emir Begagic (Medicinski glasnik, 2025)
Aim: To investigate the predictors of biochemical relapse (BCR) among patients with non-metastatic prostate cancer treated with radiotherapy as the first-line therapy. Methods: The study included 91 patients diagnosed with prostate cancer at the University Clinical Centre in Tuzla, Bosnia and Herzegovina. After the radiation treatment as the first line of treatment, the patients were monitored for the next 36 months. If patients were classified in medium and high-risk groups, hormone therapy was administered. The occurrence of BCR was determined based on prostate-specific antigen (PSA) values. Potential prognostic parameters, including Gleason score (GS), PSA, tumour size (TNM), and standardised risk classification (RC), were monitored. Results: A total of 46 (50.5%) patients were aged 66-75, with a median PSA of 14.50 ng/mL. A Gleason score <6 was found in 72 (79.1%) of patients, and 31 (34.1%) had T2c tumours. The BCR occurred in 32 (35.2%) patients, with a median relapse time of 18 months. Significant predictors of BCR were Gleason score ?6 (OR:4.46; p=0.006) and tumour stage >T2b (OR:3.59; p=0.021). The RC showed an Area Under Curve (AUC) of 0.634 (p=0.050), indicating its potential diagnostic accuracy. Conclusion: Gleason score ?6 and TNM>T2b are significant predictors of biochemical relapse in prostate cancer patients treated with radiotherapy. These results emphasize the need for additional monitoring and timely treatment of clinical disease progression in patients with Gleason score ?6 and tumour stage >T2b.
Keywords: androgen antagonists; prostate-specific antigen; radiotherapy